Acute health effects of exposure to high levels of air pollution in eastern Europe - Peters, A; Goldstein, I F; Beyer, U; Franke, K; Heinrich, J; Dockery, D W; Spengler, J D; Wichmann, H E (American journal of epidemiology, 1996)
Acute effects of winter-type air pollution characterized by high levels of SO2, moderate levels of particles, and low acidity were studied. A panel of 155 asthmatic children and 102 adults with a history of asthma from the former German Democratic Republic cities of Erfurt and Welmar and from the Czech Republic city of Sokolov participated from September 1990 through June 1992. The panelists recorded daily symptoms, medication intake, and peak expiratory flow (PEF). Statistical analysis was based on linear regression of population-averaged time series controlling for trend, meteorology, and autocorrelation. A temporospatial time series approach was also applied to the data to eliminate possible confounding by some known or unknown variables that occurred simultaneously in two of the study areas. Weak same-day effects and a stronger cumulative effect of air pollution on children was observed both for PEF and for symptoms. PEF decreased -0.90% (-1.35 to -0.46%), and a symptom score increased 14.7% (0.8-28.6%) in association with an average increase of 128 micrograms/m3 SO2 over the previous 5 days. Effects on adults were smaller and less consistent. Morbidity of children was best predicted by SO2 and sulfate concentrations. The authors conclude that prolonged, high exposure to winter-type pollution was associated with small adverse health effects in asthmatics.
Keywords: Air Pollution; vrcholová exspirační průtoková rychlost; lidé; mladiství; roční období; oxid siřičitý; Adult; Middle Aged; znečištění ovzduší; Germany; látky znečišťující vzduch; Regression Analysis; Asthma; Peak Expiratory Flow Rate; Female; dítě; Adolescent; aerosoly; Humans; Air Pollutants; Aerosols; Česká republika; počasí; lidé středního věku; Seasons; mužské pohlaví; Sulfur Dioxide; Czech Republic; ženské pohlaví; Německo; Aged, 80 and over; senioři nad 80 let; Male; Aged; regresní analýza; bronchiální astma; Child; dospělí; Weather; senioři